Thermal Intramolecular [4 + 2] Cycloadditions of Allenamides: A Stereoselective Tandem Propargyl Amide Isomerization–Cycloaddition - Lohse, Andrew G. (2009)
[Image: see text] A stereoselective intramolecular normal demand [4 + 2] cycloaddition of allenamides under thermal conditions without metal assistance is described. This work led to the development of a stereoselective tandem propargyl amide-isomerization–[4 + 2] cycloaddition sequence amenable for rapid assembly of complex nitrogen heterocycles.